Mesenchymal Stem Cell-Derived Exosome Therapy of Microbial Diseases: From Bench to Bed - Wu, Xiaolan; Jin, Shanshan; Ding, Chengye; Wang, Yu; He, Danqing; Liu, Yan (Frontiers in Microbiology, 2022)
Microbial diseases are a global health threat, leading to tremendous casualties and economic losses. The strategy to treat microbial diseases falls into two broad categories: pathogen-directed therapy (PDT) and host-directed therapy (HDT). As the typical PDT, antibiotics or antiviral drugs directly attack bacteria or viruses through discerning specific molecules. However, drug abuse could result in antimicrobial resistance and increase infectious disease morbidity. Recently, the exosome therapy, as a HDT, has attracted extensive attentions for its potential in limiting infectious complications and targeted drug delivery. Mesenchymal stem cell-derived exosomes (MSC-Exos) are the most broadly investigated. In this review, we mainly focus on the development and recent advances of the application of MSC-Exos on microbial diseases. The review starts with the difficulties and current strategies in antimicrobial treatments, followed by a comprehensive overview of exosomes in aspect of isolation, identification, contents, and applications. Then, the underlying mechanisms of the MSC-Exo therapy in microbial diseases are discussed in depth, mainly including immunomodulation, repression of excessive inflammation, and promotion of tissue regeneration. In addition, we highlight the latest progress in the clinical translation of the MSC-Exo therapy, by summarizing related clinical trials, routes of administration, and exosome modifications. This review will provide fundamental insights and future perspectives on MSC-Exo therapy in microbial diseases from bench to bedside.